Effect Of Career Development And Work Motivation On Employee Performance With Job Satisfaction As Intervening Variable At PT.Mark Dynamic Medan - Sembiring, Lea Rosa; Ronny Edward, Yusuf; Fitri Rostina, Cut (Publisher Cv. Inara, 2022)
This study aims to determine whether career development and work motivation affect employee performance through job satisfaction as an intervening variable at PT. Mark Dynamic Medan. The study was conducted on 85 employees of PT. Mark Dynamic Medan by using the Slovin formula sampling technique. The data collection technique used is primary data in the form of questionnaires and secondary data obtained through documentation studies. The data analysis technique uses quantitative data which is processed with SPSS version 25 program, namely t test, coefficient of determination (R2) and path analysis. The results obtained in this study indicate 1) there is a significant influence between career development on job satisfaction, 2) there is a significant influence between work motivation variables on job satisfaction, 3) there is a significant but not significant effect between job satisfaction variables on performance, 4) there is an influence but not significant between career development variables on performance, 5) there is a significant influence between work motivation variables on performance, 6) job satisfaction variables can affect career development variables on performance, 7) job satisfaction variables can affect work motivation variables on performance. The ability of career development variables, work motivation and job satisfaction in explaining employee performance at PT. Mark Dynamic Medan is 62.3%, while the remaining 37.7% is explained by other variables not included in this research model.